The implementation of permaculture design as a solution to achieve the food security in sub-optimal areas of Pangandaran Regency - Nasrudin Nasrudin; Firgian Ardigurnita; Kusuma Agdhi Rahwana; Saeful Iman (Universitas Muhammadiyah Magelang, 2022)
Pangandaran Regency has the potential for food development using sub-optimal land. The purpose of this community service is to implement the concept of permaculture design by empowering Farmer Groups and Livestock Groups to achieve regional food security. The methods used in this activity include socialization and counseling, demonstration plots of technology research results at several partner locations, and evaluation. Based on the results of the dissemination, the application of permaculture design on sub-optimal agricultural land is able to provide diverse food, maintain environmental sustainability, and achieve food security at the regional level.